An Analysis of Information Spreading and Privacy Issues on Social Networks - Sayin, Burcu; Şahin, Serap; Sayın, Burcu (Izmir Institute of Technology, 2017)
With Social Networks (SNs), being populated by a still increasing number of people, who take advantage of the communication and collaboration capabilities that they offer, density of the information, spread over SNs is increasing steadily. Furthermore, the probability of exposure of someone’s personal moments to a wider than expected crowd is also increasing. Hence, analyzing the spreading area and privacy level of any information through a SN is an important issue in social network analysis. By studying the functionalities and characteristics that modern SNs offer, along with the people’s habits and common behavior in them, it is easy to understand that several privacy risks may exist, for many of which people may be unaware of. We address this issue, focusing on interactions with posts in a SN, using Facebook as the research domain. As a novelty, we propose an application tool which visualizes the effect of potential privacy risks in Facebook and provides users to control their privacy. The proposed (and simulated) tool allows a Post Owner to observe the spreading area of his/her post, depending on the selected privacy settings of this post. Moreover, it provides preliminary feedback for all the Facebook users that have interacted with this post, to make them aware of the possible privacy changes, aiming to give them a chance to protect the privacy of their interaction on this post by deleting it when such a privacy change takes place.

Sosyal Ağlar (SA)’ın insanlara sağladığı haberleşme ve işbirliği yapma avantajları ile birlikte, kullanıcı sayısı ve SA üzerinde yayılan bilginin yoğunluğu da giderek artmaktadır. Buna ek olarak, bir kimseye ait özel bilgilerin, paylaşmayı beklediği insan topluluğundan daha büyük bir alanda görülebilme olasılığı da artmaktadır. Bu nedenle, SA üzerinde bilginin yayılımının ve mahremiyetinin analizi SA’nın analizinde önemli bir problemdir. Modern SA’nın sunduğu servisler, insanların alışkanlıkları ve ortak davranışları ile bir araya geldiğinde, birçok insanın farkında bile olmadığı mahremiyet risklerini oluşturabilir. Tez çalışmasında bu problem hedeflenmiştir. Facebook araştırma alanı olarak kullanılmış ve SA’da kullanıcılar ile gönderiler arasındaki etkileşimlere odaklanılmıştır. Yenilik olarak, Facebook’taki potansiyel mahremiyet risklerinin etkisini görselleştiren ve kullanıcılara mahremiyetlerini kontrol altında tutma olanağı sağlayan bir uygulama aracı sunulmuştur. Önerilen ve benzetimi yapılan bu araç; gönderi sahibine, seçmiş olduğu gizlilik ayarlarına göre gönderisinin yayılım alanını gözlemleme şansı vermektedir. Ek olarak, bu gönderiyi beğenerek ve/veya yorum yaparak iletişime geçmiş olan SA kullanıcılarının mahremiyet konusunda farkındalığını arttıracak ve mahremiyetlerini koruyacak bir çözüm sunulmaktadır. Bunu sağlamak için, gönderinin gizlilik ayarı değiştirildiğinde, bu gönderiyi beğenmiş ve/veya yorum yapmış olan kullanıcılara, önerilen araçtan bir geribildirim iletilebilmekte ve hatta bu tip durumlarda beğenilerinin/yorumlarının otomatik olarak silinmesi sağlanabilmektedir.
Sosyal Ağlarda Bilginin Yayılımı ve Mahremiyet Konularının Analizi
Thesis (Master)--Izmir Institute of Technology, Computer Engineering, Izmir, 2017
Full text release delayed at author's request until 2020.01.04
Includes bibliographical references (leaves: 50-55)
Text in English; Abstract: Turkish and English
Keywords: Social networks; Information security; Information sharing; Privacy; Big data; Data analysis